Adaptability assessment of the whitecap statistical physics model with cruise observations under high sea states - Shi, Yongfang; Yang, Yongzeng; Qi, Jinpeng; Wang, Haili (Frontiers in Marine Science, 2025)
Whitecaps are crucial for understanding ocean-atmosphere interactions, particularly under high sea states, where quantifying whitecap coverage has long been a key research focus. This study aims to validate the Whitecap Statistical Physics Model (WSPM) under high sea states using observational data. Observational data from the High Wind Speed Gas Exchange Study (HiWinGS) was used to validate the WSPM. The model's performance was assessed across multiple sites under wind speeds exceeding 15 m/s and significant wave heights (SWH) up to 10 meters. The WSPM showed good agreement with observational data at most sites, accurately capturing variations in whitecap coverage. At the same time, discrepancies in the model results were observed, which were attributed to errors in the WSPM's data sources and complex sea conditions characterized by rapid shifts in wind direction and alternating dominance of wind waves and swell. This study highlights the advantages of physics-based models over simple wind-speed-dependent parameterizations in capturing the complexities of wave dynamics. The findings suggest that the WSPM is highly effective in capturing the dynamics of whitecap coverage across a range of high sea states, providing a detailed and robust reference for its application in real-world scenarios. Further research is needed to address the sources of error and improve the model's accuracy under complex sea conditions.